Patterns of errors and weaknesses in the diagnostic process: retrospective analysis of malpractice claims and adverse events from two national databases - Kim Lyngby Mikkelsen; Charlotte Frendved; Siri Tribler; Eva Benfeldt; Rikke Mørch Jørgensen (BMJ Open Quality)
Background Diagnostic errors (DEs) are a significant global patient safety issue, often associated with increased morbidity and mortality due to overlooked, delayed, or incorrect diagnoses. Our aim was to study the occurrence of DEs and adverse events (AEs), patient-related harm to identify vulnerable steps in the diagnostic process.Methods A retrospective analysis of data from two public, national databases—National Health Care Compensation Claims Database (2009–2018) and Danish Patient Safety Database with AEs (2015–2020). Vulnerable steps in the diagnostic process were identified using a scoring tool developed by The Controlled Risk Insurance Company.Results In the analysis of patient compensation claims, 14.5% of all settled cases (n=90 000) were classified as due to a DE, with a 59% compensation rate for DEs, twice the rate compared with other compensated cases (25%). DEs constituted 29% of all compensated cases. Death due to DEs was 8.3% (n=680 cases), 1.8 times higher compared with other cases and DEs resulted in higher degrees of disability.In the overall reported AEs, 0.3% of AEs were fatal and 1.7% AEs caused severe patient harm, per year. In a representative sample of AEs with a severe or fatal consequence (n=269), 33% were due to DEs.The initial clinical assessment was a cause or contributor to the DE in 80% of the compensation cases and in 83% of the severe or fatal AEs. The follow-up and coordination phase were a cause in 33% of compensation cases and 46% of severe or fatal AEs.Conclusions Errors and AEs in the diagnostic process are prevalent and a significant patient safety issue in Danish healthcare. This study identifies vulnerable steps in the diagnostic process, with patterns correlated to different degrees of severity, and highlights steps for future improvements efforts needed to mitigate the risk of DEs.